Borrowing Agreement with the Bank of Finland. (Policy Papers; Policy Paper ;, 2010)
This paper is one in a series of follow-up papers on The Fund's Mandate-An Overview and The Fund's Mandate-The Legal Framework discussed by the Executive Board on February 22, 2010. This paper proposes ideas to modernize the mandate and modalities of surveillance. It addresses how the Fund might increase the value of its surveillance by considering both the substance of surveillance (what it should do) and its modalities (how to do it). The main ideas focus on how the Fund can do more-and more sharply defined-multilateral surveillance, generate greater value and traction from bilateral surveillance, and integrate the two better. Options to buttress multilateral surveillance include doing more analysis of outward spillovers, holding multilateral consultations as needed on special topics to foster collaboration and collective action, and strengthening financial sector surveillance by mapping interconnectedness across borders and sectors and the transmission channels of macro-financial instability. The adoption of Multilateral Surveillance Decision could help support these ideas. Options to increase the value and traction of bilateral surveillance include promoting better cross-country understanding, with more thematic multi-country reports, producing more timely and topical reports, and increasing outreach and engagement with stakeholders.